The hydrology of a temperate fluvial estuary in early winter - Vaz, N. (2015)
In order to evaluate how current speed, salinity and water temperature stratification behaves under the influence of a freshwater so urce in a tidal domain, a 25 hour survey campaign was performed in the upper sector of the Vouga River estuary, the major source of freshwater of Ria de Aveiro, a coastal lagoon located in the Northwest of the Iberian Peninsula. The sampling campaign started at 10:30 AM of January 15 th 2004 and ended next day, covering two tidal cycles, during neap tide condition (tidal range of about 1.7 m) and low river runoff (58 m 3 s -1 ). Observations of the thermohaline properties and currents were undertaken in an anchor station located about 9 km upstream of the mouth of the lagoon. Local meteorological variables were also measured. Vertically lunar hourly profiles of salinity, water temperature and current speed were obtained and the results indicate that the estuary is forced by semi-diurnal tides. The profiles of current intensity indicated an asymmetry between flood ( v >0) and ebb ( v <0) being the ebb currents higher than the flood ones, with maximum values of about -1.1 and 0.7 ms -1 , respectively. The major ebbing velocity was enhanced by the freshwater runoff. The lunar hourly variations of salinity and water temperature reveal that during the ebb, the vertical stratification decreases, increasing during the flood period. The salinity ranges between 0 and 32 psu and the water temperature between 10.9 and 13.7 ºC. Near the surface, the water temperature is influenced by the air temperature, decreasing along the day. At mid-water and near the bed the salinity and water temperature increases during the flood periods, decreasing during the ebb. From the time mean salinity and current profiles for the 25 hours period were obtained the stratification and circulation parameters of the classical Stratification-Circulation Diagram (Hansen and Rattray, 1966), revealing that the estuary can be considered partially-mixed.